Intracranial subdural hematoma after spinal anesthesia for cesarean section: Case report and review of literature - Uma Srivastava; Archna Agrawal; Amrita Gupta; Yogita Dwivedi; Sathiyanarayanan Pilendran; Vinay Shukla (Wolters Kluwer Medknow Publications, 2014)
Subdural hematoma (SDH) is a rare but serious complication of spinal anesthesia. We report a case of intracranial SDH in a patient developing 11 days after spinal anesthesia for cesarean section. The patient complained of headache on the 2nd post-operative day that was relieved by analgesics, bed rest and hydration. Later she presented with severe headache, vomiting, dizziness, dysarthria, irritability and somnolence. Diagnosis of the left sided SDH was confirmed radiologically and treated surgically. The patient recovered completely. The report highlights the need of considering the possibility of SDH in patients when postdural puncture headache is prolonged or recurs after a headache free period with neurological symptoms.